Theory of Change Analysis: Building Robust Theories of Change - Mayne, John (Canadian Journal of Program Evaluation, 2017)
Models for theories of change vary widely as do how they are used. Wha t constitutes a good or robust theory of change has not been discussed much. This article sets out and discusses criteria for robust theorie s of change. As well, it discusses how these criteria can be used to u ndertake a vigorous assessment of a theory of change. A solid analysis of a theory of change can be extremely useful, both for designing or assessing the designs of an intervention as well as for the design of monitoring regimes and evaluations. The article concludes with a discu ssion about carrying out a theory of change analysis and an example.